2016
DOI: 10.1158/1940-6207.capr-15-0269
|View full text |Cite
|
Sign up to set email alerts
|

Exemestane Use in Postmenopausal Women at High Risk for Invasive Breast Cancer: Evaluating Biomarkers of Efficacy and Safety

Abstract: This phase II trial evaluated clinical markers of efficacy and safety of exemestane in postmenopausal women at increased risk for breast cancer. Postmenopausal women (n=42) at risk for invasive breast cancer received 25mg exemestane daily for two years along with calcium and vitamin D. The primary outcome was change in mammographic density (MD) after one year. Secondary outcomes included change in serum steroid hormones as well as change in trefoil protein 1 (TFF1) and proliferating cell nuclear antigen (PCNA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 49 publications
(62 reference statements)
1
19
0
Order By: Relevance
“…Of six relevant studies, three uncontrolled studies showed MD reductions with two reaching significance [32, 43, 44]. Three further trials with control arms demonstrated no MD reduction relative to untreated patients, although numbers in all trials were low [4547].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of six relevant studies, three uncontrolled studies showed MD reductions with two reaching significance [32, 43, 44]. Three further trials with control arms demonstrated no MD reduction relative to untreated patients, although numbers in all trials were low [4547].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the proven therapeutic efficacy of aromatase inhibitors (AIs) in the adjuvant setting [ 42 ], MD has not been observed to change consistently or significantly in response to these agents (Table 2 ). Of six relevant studies, three uncontrolled studies showed MD reductions with two reaching significance [ 32 , 43 , 44 ]. Three further trials with control arms demonstrated no MD reduction relative to untreated patients, although numbers in all trials were low [ 45 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, Tff1, Sprr2a1, and Aldh3b2 have not previously been implicated in adenomyosis. Tff1 is an estrogen response gene that has been reported to be a potential tumor marker in the diagnosis of breast cancer 434546 that encodes small proline-rich protein (SPRR)2a, which is a member of the SPRR family.…”
Section: Discussionmentioning
confidence: 99%
“…Tff1 is an estrogen response gene that has been reported to be a potential tumor marker in the diagnosis of breast cancer. 43 45 Sprr2a is an estrogen-responsive gene 46 that encodes small proline-rich protein (SPRR)2a, which is a member of the SPRR family. This binds to and activates SH3 domain-containing proteins, resulting in physiological effects in a broad range of tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Exemestane is an aromatase inhibitor (AI) with demonstrated efficacy in reducing the incidence or recurrence of breast cancer in postmenopausal women [1][2][3]. However, menopause-related side-effects due to estrogen suppression from exemestane can limit uptake and adherence.…”
Section: Introductionmentioning
confidence: 99%